Hematological and histological Changes in mice Fed Aqueous Extract of Senna alexandrina - AL-Taie, Mustafa A. K. (Iraqi Journal of Science, 2019)
This study aims to evaluate the effect of aqueous extract stem of dried of Senna Alexandrıa using male mıce once daily at varying doses for 2 and weeks on hematological and histological changer in liver and kidney. In the acute toxicity aqueous extracted of dried stem of Senna Alexandrıa were administrated orally to mice up to 20-25 gr of body weight, in sub-acute study mice was daily administrated orally with same extraction at dose 500,1000,2000 mg/kg for 14 days . Hematological findings have shown in male group increase of RBC, HGB, HCT in increase of PIT in group treated with 500mg/ kg of body weight. Body weight was increase after application of extract at the dose of 1000 and 2000 mg/ kg . The histology in liver includes congestion of central vein with inflammatory cell in their lamen, vascular dilation ,fatty infiltrations cytoplasmic vacillation necrotic hepatocyte . Whereas in the kidney the changer includes shrunken glomeruli increasing of renal space, swelling and cytoplasmic vaculation of epithelial cells lining the renal tubule. Increase in body weight was with a dose 1000,2000mg/kg week after 2 weeks.